Municipal Waste Map: a Case Study of Guimarães, Portugal - Sepúlveda, Dalila; Loureiro, Isabel; Vilarinho, Cândida; Carvalho, Joana (European Journal of Sustainable Development, 2016)
Guimarães is located in the north of Portugal, is a middle size town, which historic centre is UNESCO World Heritage. The city was also European Cultural Capital by 2012 and in 2013 was European City of Sports. Currently, is running for European Green Capital 2020, being the Waste Production and Management (WPM) one of the strategic guideline. Taking into account the WPM policy and the city goals, a Municipality Strategic Waste Plan (2016-2025) (SWP), will be done. Guimarães is considered to be a “diffuse territory”, as it encompasses land use and economic activity development, leading to different scenarios. It is also important to notice that 1/3 of the Guimarães population is located on the urban area. Under this context, the WPM across the Municipality will be directly affected by specific features of the urban population, and the correlation between several other variables shall be considered in a holistic approach comprising waste production characterization, land use, citizens socio demographic aspects and human resources. This project aims at presenting a first approach to the definition of the SWP, in the form of an integrated Roadmap of waste production, in a multi-disciplinary approach between the land use and the socio-demographic characteristics. Keywords: Waste Management Plan, holistic approach, Municipal waste.